求证,2(cosA-sinA)/(1+sinA+cosA)=cosA/(1+sinA)-sinA/(1+sinA)

1个回答

  • cosA/(1+sinA)-sinA /(1+cosA)

    =[cosA(1+cosA)-sinA(1+sinA)] / [(1+sinA)(1+cosA)

    =(cosA+cos^2A-sinA-sin^2A) / (1+sinA+cosA+sinAcosA)

    =[(cosA-sinA)+(cosA+sinA)(cosA-sinA)] / {1+sinA+cosA+1/2[(cosA+sinA)^2-1]}

    =(cosA-sinA)(cosA+sinA+1) / [1+sinA+cosA+1/2[(1+cosA+sinA)(cosA+sinA-1)]

    =(cosA-sinA)(cosA+sinA+1) / {(1+sinA+cosA)[1+1/2(cosA+sinA-1)]}

    =(cosA-sinA) / [1+1/2cosA+1/2sinA-1/2]

    =2(cosA-sinA) / (1+cosA+sinA),得证.